Infiltration of aluminum in 3D‐printed metallic inserts. Issue 1 (19th September 2022) - Nunes, Helder; Emadinia, Omid; Costa, José; Madureira, Rui; Soares, Rui; Silva, José; Frada, Inês; Anjos, Vitor; Viana, Filomena; Vieira, Manuel; Reis, Ana
Abstract: Aluminum structural composites through the infiltration process can be performed by vacuum, centrifugal, or squeeze casting, involving the infiltration of molten Al into fibers, particles, foams, or even porous preforms. This methodology creates hybrid structures of two distinct metal alloys that can be used to locally strengthen components or even to improve the properties of bulk materials, such as ultimate tensile strength and thermal conductivity. New approaches involve the infiltration of liquid Al into a three‐dimensional (3D)‐printed structure of the more rigid metal, such as steel, that the Al matrix. In the current study, stainless steel and copper inserts were produced by fused filament fabrication techniques with various geometries. Moreover, some 3D inserts were electrochemically coated with pure copper to enhance the wettability of the steel insert by Al. Then, the infiltration of these inserts was evaluated by gravity casting, centrifugal casting, and low‐pressure sand casting (LPSC). Evaluations involved microstructural characterization using optical microscopy and SEM for interface analysis. It is revealed that centrifugal casting is highly reliable to infiltrate the inserts with Al, filling detailed cavities in depth. The copper coating aided in the creation of intimate interfaces. The infiltration at the insert's surfaces, curved‐like topography, is obtained through LPSC though it is affected by the direction in respect of material flow. Abstract : Structural composites can be created through the infiltration of liquid aluminum into a three‐dimensional (3D)‐printed structure of the more rigid metal, such as steel. Gravity, centrifugal, and low‐pressure sand casting (LPSC) were the researched casting techniques for infiltration in the current study. From the techniques studied, centrifugal casting appears to be a viable way to infiltrate Al melt into small details and complex geometries, thus producing structural composites.